EFFECT OF RAM EXPOSURE ON ESTRUS SYNCHRONIZATION AND CONCEPTION UNDER TWO SYSTEMS OF FEEDING STRATEGIES IN NARI SUWARNA EWES - RAVINDRANATH, B M; MURTHY, V CHANDRASHEKARA; KRISHNASWAMY, A (The Indian Journal of Animal Reproduction, 2023)
The present study was aimed to investigate the effect of ram presence on estrus characteristics in NARISuwarna ewes. Forty eight ewes were equally divided into two groups as per the type of feeding management.Ewes in each group again divided into two subgroups (n=12), according to the presence or absence of ramduring estrus synchronization protocol by using progesterone intravaginal sponges for 12 days. The time takenfor onset of estrus, duration of estrus and conception rate in presence and absence of ram was 24.99±0.61 hand 28.63±0.97 h; 34.57±1.26 h and 39.68±1.35 hand 83.3 % and 75 % respectively under scientific feeding.Similarly, 27.54±1.13 h and 30.94±1.11 h; 35.11 ±1.97 h and 40.31±2.26 h and 75 % and 66.6 % for onset ofestrus, duration of estrus and conception rate in presence and absence of ram respectively under pasturegrazing. Further, it was concluded that the presence of ram significantly reduced the time of onset of estrus butnot the duration of estrus and conception rate in both the groups.
Keywords: NARI Suwarna; Ram effect; Estrus and conception